Lipids profile and thyroid parameters in patients with type 2 diabetes mellitus - Yuzvenko, T. (Journal of Education, Health and Sport, 2016)
Yuzvenko T. Lipids profile and thyroid parameters in patients with type 2 diabetes mellitus. Journal of Education, Health and Sport. 2016;6(3):227-232. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55173 http://ojs.ukw.edu.pl/index.php/johs/article/view/3569 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 20.03.2016. Accepted: 23.03.2016. LIPIDS PROFILE AND THYROID PARAMETERS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS T. Yuzvenko Ukrainian Research and Practice Center of Endocrine Surgery, Transplantation of Endocrine Organs and Tissues, Health Ministry of Ukraine, Kyiv Abstract Background Higher level of thyroid-stimulating hormone (TSH) and lower thyroid hormone levels within the euthyroid range may adversely affect atherosclerosis. The aim of this study was to investigate the potential association between thyroid parameters and lipids profile in a cohort of euthyroid diabetic patients. Methods. Two hundred and thirty-one euthyroid patients with type 2 diabetes mellitus (151 males and 80 females) were consecutively recruited. Clinical and anthropometric data was collected from all participants. Whole blood samples were drawn in the morning after an overnight fasting for the measurement of serum TSH, free thyroxine (fT4), free triiothyronine (fT3), anti-thyroid peroxidase antibody (TPO-Ab) levels, as well as lipid concentrations and glucose. Results TSH was higher in females than males. Stratified by TSH, high-density lipoprotein cholesterol (HDL-c) level increased in subjects with TSH ≥2.5 uIU/mL (p = 0.003). In females, total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-c) level was significant lower in subjects with TSH <2.5uIU/mL. TSH was significantly associated with TC and LDL-c. In a multiple linear regression analysis (stepwise), TSH was positive associated with TC and LDL-c. Among all patients 49 (21.2%) were TPO antibody positive. The blood pressure and lipid levels were lower in TPO-Ab positive patients, however, the differences were not significantly. Conclusions. TSH was positively associated with serum TC and LDL-c in euthyroid women with type 2 DM. Analysis in the subgroup having TPO antibody assays demonstrating non-significantly lower TC levels among seropositive subjects was consistent with the above stated consideration for women as a whole. Further investigations are needed to understand the intimate mechanisms of lipid metabolism in type 2 diabetes with respect to thyroid function. Key words: type 2 diabetes mellitus, thyroid parameters, lipids profile.